Service level agreement checking in cloud computing in terms of verification and validation concepts - Mohd Jamail, Nor Shahida; Atan, Rodziah (The Society of Digital Information and Wireless Communications (SDIWC), 2013)
Nowadays, cloud computing is a very interesting environment for researcher to look deep. It is more on computing delivery whereby service rather than a product. It provides infrastructure as a service (IaaS), platform as a service (PaaS), software as a service (SaaS), and storage as a service. This technology is not involved end-user knowledge of the physical location and configuration of the system when users deliver the services. The cloud computing concepts is derived from grid computing, whereby end-user no need to understand the devices and components or infrastructure required in retrieved the service. It is based on virtualization resources. Cloud computing is consider as a new area in research and there have a lots of problem especially regarding to Service Level Agreement (SLA). This research is focusing to verify whether the SLA is follow the contract or violated. All the results are used for validation of the cloud services based on its own SLA.